2023
DOI: 10.1002/csc2.20923
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of alfalfa interseeded into corn in response to one cycle of selection and hybridization

Abstract: Intercropping alfalfa (Medicago sativa L.) in corn (Zea mays L.) can improve forage production, but wet growing conditions and high corn yields adversely impact alfalfa establishment. Therefore, we evaluated breeding alfalfa specifically for intercropping by selecting surviving plants from previous alfalfa varietal evaluations under corn and assigning them to five polycrosses to form cycle-1 synthetics. Pollen from four polycrosses was also used to generate hybrid seed using a male-sterility system. Corn was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Application of PHD growth retardant and delayed interseeding usually reduced alfalfa plant height, but only the latter treatment was associated with improved yield of the maize silage companion crop, presumably because late seeding reduced the overall growth and early season competitiveness of alfalfa. By contrast, PHD treatment has little effect on leaf growth but reduces stem growth and enhances root growth in alfalfa (Grabber, Osterholz et al., 2021; Grabber, Riday et al., 2023) and these morphological shifts apparently had no impact on alfalfa's competitive effect on maize under the conditions of these studies.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Application of PHD growth retardant and delayed interseeding usually reduced alfalfa plant height, but only the latter treatment was associated with improved yield of the maize silage companion crop, presumably because late seeding reduced the overall growth and early season competitiveness of alfalfa. By contrast, PHD treatment has little effect on leaf growth but reduces stem growth and enhances root growth in alfalfa (Grabber, Osterholz et al., 2021; Grabber, Riday et al., 2023) and these morphological shifts apparently had no impact on alfalfa's competitive effect on maize under the conditions of these studies.…”
Section: Resultsmentioning
confidence: 66%
“…Identical to system 1 but with prohexadione (PHD) growth retardant sprayed onto alfalfa to enhance seedling survival (Grabber, Smith et al., 2021; Grabber, Dias, & Renz, 2023).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent experiments were initiated in 2019 and 2020 at the Arlington Agricultural Research Station (43 • 18 N, 89 • 20 W) on a Plano silt loam (fine-silty, mixed, superactive, mesic Typic Argiudolls). The Arlington Station was chosen for this study because previous multilocation intercropping studies [8,17] indicated conditions at this location fostered relatively high levels of foliar damage and death of alfalfa seedlings under corn. Corn silage was grown prior to the 2019 study, and soybeans were grown prior to the 2020 study.…”
Section: Sites and Crop Managementmentioning
confidence: 99%
“…However, the clear benefits of fungicide and insecticide treatments on seedling health, vigor, and survival, especially under wet growing conditions, suggest that disease and perhaps insect pests play a large role in determining the success of alfalfa establishment under corn. Breeding new alfalfa varieties with greater survival under corn is one option for improving establishment in this system [17]. Further work to identify more effective agrichemical treatments and other improved management practices is also needed to ensure interseeding can be successfully realized under a wide range of production environments.…”
Section: Stand Density and Groundcover Of Alfalfa Following Establish...mentioning
confidence: 99%